Imaging of Spine Infections - Chianca, Vito; Chalian, Majid; Harder, Dorothee; Del Grande, Filippo (Seminars in Musculoskeletal Radiology, 2022)
The incidence of spondylodiskitis has increased over the last 20 years worldwide, especially in the immunodepressed population, and it remains a complex pathology, both in terms of diagnosis and treatment. Because clinical symptoms are often nonspecific and blood culture negative, imaging plays an essential role in the diagnostic process. Magnetic resonance imaging, in particular, is the gold standard technique because it can show essential findings such as vertebral bone marrow, disk signal alteration, a paravertebral or epidural abscess, and, in the advanced stage of disease, fusion or collapse of the vertebral elements. However, many noninfectious spine diseases can simulate spinal infection. In this article, we present imaging features of specific infectious spine diseases that help radiologists make the distinction between infectious and noninfectious processes.
Keywords: spondylodiskitis; pyogenic; spine infection; tuberculosis; modalities